A decade of on-farm data about improved cereal and legume cropping in Mexico - Gardeazabal, Andrea; Cabello, Alberto; Fonteyne, Simon; Jiménez, Benancio; Leal Gonzalez, Abel Jaime; Nuñez Jimenez, Daniel; Odjo, Sylvanus; Pacheco Rodríguez, Guadalupe Montserrat; Ramírez Ortega, Maria de Lourdes; Van Loon, Jelle; Vargas-Rojas, Luis; Verhulst, Nele; et al. (Nature Publishing Group, 2025)
This data descriptor presents a decade-long agronomic dataset collected between 2012 and 2022 by extension agents across Mexico as part of CIMMYT’s on-farm experimentation network. Extension agents used a unified digital logbook platform (BEM, later e-Agrology) to record agronomic activities, farm operations, and results. After multi-stage cleaning and validation, the dataset comprises 69,008 logbooks from 10,763 innovation plots testing new technologies, 10,305 control plots under conventional management, and 47,940 extension plots adopting sustainable practices. Key variables cover crop management (including sowing and harvest dates), resource use (including inputs, fuel and labor), activity costs, market prices, and yields for maize (Zea mays), beans (Phaseolus vulgaris), wheat (Triticum aestivum, Triticum durum), sorghum (Sorghum bicolor), and barley (Hordeum vulgare). Spanning diverse agroecologies and farm sizes, this open-access resource enables analyses of long-term productivity trends, cost–benefit relationships, input–output efficiencies, and climate-related performance. By providing harmonized, field-level data across multiple management scenarios, it can be used to derive valuable insights for researchers, extension services, and policymakers to develop optimized agronomic recommendations and sustainable intensification strategies.